Genetic‐Code‐Expansion Strategies for Vaccine Development - Fok, Jelle A. (Chembiochem, 2020)
Abstract: By providing long‐term protection against infectious diseases, vaccinations have significantly reduced death and morbidity worldwide. In the 21st century, (bio)technological advances have paved the way for developing prophylactic vaccines that are safer and more effective as well as enabling the use of vaccines as therapeutics to treat human diseases. Here, we provide a focused review of the utility of genetic code expansion as an emerging tool for the development of vaccines. Specifically, we discuss how the incorporation of immunogenic noncanonical amino acids can aid in eliciting immune responses against adverse self‐proteins and highlight the potential of an expanded genetic code for the construction of replication‐incompetent viruses. We close the review by discussing the future prospects and remaining challenges for the application of these approaches in the development of both prophylactic and therapeutic vaccines in the near future.